2015
DOI: 10.1176/appi.ps.201400097
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Recurrent Use of Psychiatric Emergency Services

Abstract: Patients with personality disorders and past recurrent use of emergency services appeared to rely more on psychiatric emergency services for continuous psychiatric care than patients without past recurrent use of emergency services and patients with mood, substance use, anxiety, or psychotic disorders. Creation of a follow-up treatment program for this clinical population within the psychiatric emergency setting itself may provide better access to care for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 17 publications
(61 reference statements)
2
38
0
1
Order By: Relevance
“…4 Individuals with personality disorders have been associated with high frequency utilisation of emergency departments, [5][6][7][8][9] and recurrent use of emergency room psychiatric services. 10 A recent Canadian study found that individuals who were frequent emergency department presenters had an increased odds of having a primary or comorbid personality disorder diagnosis and that 87% of individuals with antisocial personality disorder or borderline personality disorder (BPD) presented five or more times in one year. 11 Stigma further complicates the interaction between the healthcare system and individuals with personality disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Individuals with personality disorders have been associated with high frequency utilisation of emergency departments, [5][6][7][8][9] and recurrent use of emergency room psychiatric services. 10 A recent Canadian study found that individuals who were frequent emergency department presenters had an increased odds of having a primary or comorbid personality disorder diagnosis and that 87% of individuals with antisocial personality disorder or borderline personality disorder (BPD) presented five or more times in one year. 11 Stigma further complicates the interaction between the healthcare system and individuals with personality disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Findings regarding increased frequency of emergency department presentation, increased likelihood of recurrent emergency department visits, and age and gender of individuals with personality disorders presenting to the emergency departments were consistent with previously published studies. 1,[5][6][7][8][9][10][11] Surprisingly, only 6% of mental-health-related presentations in the emergency departments involved individuals with a personality disorder diagnosis. Evidence suggests that personality disorder, in particular BPD, is 'markedly under-diagnosed'.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation may be that satisfaction with services was lower among frequent public ambulatory health service users due to their more serious needs (Fortin et al, ). According to the literature, frequent health services users are also those who receive inadequate treatment or insufficient continuity of care; they are often high users of emergency departments in particular (Richard‐Lepouriel et al, ). Elevated levels of user satisfaction with services were also associated with better quality of life in previous studies of individuals with serious MHD (Furrer et al, ; Nasrallah, Targum, Tandon, McCombs, & Ross, ; Petkari & Pietschnig, ), which seems reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent Swedish study, persons making frequent PES visits constituted 8.1% of the total sample, yet they accounted for 38.3% of all visits made during the investigated 3 years (Schmidt, Ekstrand, & Bengtsson Tops, 2018a). Previous research arrived at similar results, finding that this relatively small group is responsible for a disproportionately high number of visits in both Scandinavian (Aagaard et al, 2014) and international contexts, including North America (Chaput & Lebel, 2007;Lincoln et al, 2016), Europe (Boyer et al, 2011;Ledoux & Minner, 2006;Richard-Lepouriel et al, 2015), and Australia (Wooden, Air, Schrader, Wieland, & Goldney, 2009;Zhang, Harvey, & Andrew, 2011). Thus, it is a global phenomenon regardless of the healthcare system.…”
Section: Introductionmentioning
confidence: 74%
“…This diverse group also reportedly does not receive or has difficulties complying with aftercare (Bruffaerts, Sabbe, & Demyttenaere, 2005), can be uncooperative (Pasic et al, 2005), and has unreliable social support (Pasic et al, 2005). Furthermore, persons who frequently visit PES are more likely to be prematurely discharged (Botha et al, 2010); suffer from personality disorders (Richard-Lepouriel et al, 2015), substance abuse disorder (Bruffaerts et al, 2005;Ledoux & Minner, 2006), and schizophrenia (Aagaard et al, 2014); and have a history of hospitalization (Pasic et al, 2005). While useful in identifying the characteristics of this group, all of these are quantitative studies and have not focused on explaining what aspects apart from demographics and diagnostics could identify the needs of these persons that make them frequently visit PES.…”
Section: Introductionmentioning
confidence: 99%